2016
DOI: 10.1016/j.cub.2016.07.073
|View full text |Cite
|
Sign up to set email alerts
|

Determination of EGFR Signaling Output by Opposing Gradients of BMP and JAK/STAT Activity

Abstract: A relatively small number of signaling pathways drive a wide range of developmental decisions, but how this versatility in signaling outcome is generated is not clear. In the Drosophila follicular epithelium, localized epidermal growth factor receptor (EGFR) activation induces distinct cell fates depending on its location. Posterior follicle cells respond to EGFR activity by expressing the T-box transcription factors Midline and H15, while anterior cells respond by expressing the homeodomain transcription fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Regarding the latter question, one difference in these signaling events is that early processes require only low levels of Grk signaling, while later processes involve higher levels of ligand; that is, weak loss-of- function mutations do not affect posterior patterning, only dorsal patterning (Schüpbach, 1987). In addition, a recent study demonstrates that the different consequences of Grk signaling in the dorsal-anterior versus the posterior follicle cells is due to the cooperative action of Grk with two additional signaling pathways: the Dpp pathway, which is activated in the anterior as discussed above, and the JAK/STAT pathway, which is activated by the ligand Unpaired in the posterior (Fregoso Lomas et al, 2016). Signaling by Grk and Dpp together results in expression of Mirror (Mirr), a dorsal fate determinant discussed below.…”
Section: Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the latter question, one difference in these signaling events is that early processes require only low levels of Grk signaling, while later processes involve higher levels of ligand; that is, weak loss-of- function mutations do not affect posterior patterning, only dorsal patterning (Schüpbach, 1987). In addition, a recent study demonstrates that the different consequences of Grk signaling in the dorsal-anterior versus the posterior follicle cells is due to the cooperative action of Grk with two additional signaling pathways: the Dpp pathway, which is activated in the anterior as discussed above, and the JAK/STAT pathway, which is activated by the ligand Unpaired in the posterior (Fregoso Lomas et al, 2016). Signaling by Grk and Dpp together results in expression of Mirror (Mirr), a dorsal fate determinant discussed below.…”
Section: Patterningmentioning
confidence: 99%
“…Signaling by Grk and JAK/STAT together results in expression of Mid and H15. Furthermore, Mid/H15 and Mirr mutually repress each other, potentially allowing for a switch-like response between the anterior and posterior interpretations of the Grk signal (Fregoso Lomas et al, 2016). …”
Section: Patterningmentioning
confidence: 99%
“…To activate EGFR signaling in the FCs, we expressed a dominant active EGFR using UAS-λtop (Queenan et al 1997). Previous work has shown that ectopic expression of these two signaling components is sufficient to convert AFCs and main body follicle cells into PFCs (Fregoso Lomas et al 2016). However, to confirm that this was the case, we stained control and ectopic expression egg chambers using an antibody against Midline (Mid), which is expressed specifically in the PFCs (Fregoso Lomas et al 2013; Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Together, JAK/STAT and EGFR activity produce the posterior follicle cell (PFC) fate (Xi et al 2003). Previous work has demonstrated that by removing JAK/STAT or EGFR it is possible to disrupt PFC formation, and that ectopic activity of both pathways in the follicle cells can induce ectopic PFCs (Xi et al 2003; Fregoso Lomas et al 2016). In the Drosophila egg chamber, EGFR signaling activates the conserved MAPK/ERK signaling cascade (Schnorr and Berg 1996); consequently, disrupting the components of this cascade can also interfere with PFC specification.…”
mentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) is a transmembrane protein involved in a broad range of developmental processes and human cancers, including glioblastoma, neck and head cancer, colorectal cancer, and non-small-cell lung cancer [9,10,11]. It has been shown that 40–50% of glioblastoma patients have dysregulated EGFR, and approximately half of these co-express the mutant receptor EGFR variant III (EGFRvIII) [12].…”
Section: Introductionmentioning
confidence: 99%